2019
DOI: 10.21203/rs.2.18679/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin nanomicelle versus curcumin improves lipid profile, stress oxidative factors and inflammatory markers in patients undergoing coronary elective angioplasty; A Randomized Clinical Trial

Abstract: Background: Curcumin exhibited antioxidant and anti-inflammatory effects. The aim of this study, assess and compare curcumin and nano-curcumin effects on lipid profile, oxidative stress index and inflammatory factors of heart patients. Methods: This Randomized, Double-Blind, Placebo-Controlled Clinical Trial conducted on 90 patients undergoing coronary elective angioplasty. Patients were randomly divided into 3 groups. The first group received a 500 mg capsule of curcumin daily. The second group received an 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, nanoformulations of curcumin could also be engineered for longer-retention, sustained release, and penetration across the mucus barrier ( Sung et al, 2007 ). Clinical studies of liposomal curcumin, microparticle curcumin, and micelle curcumin by oral delivery have been found to be safe ( Yallapu et al, 2015 ) and shown to be effective in reducing markers of oxidative stress ( Helli et al, 2021 ). Animal studies have shown that inhalable curcumin effectively mitigates lethal bacterial pneumonia ( Zhang et al, 2019 ).…”
Section: Nanoformulation Of Curcumin For Pulmonary Delivery: An Altermentioning
confidence: 99%
“…Furthermore, nanoformulations of curcumin could also be engineered for longer-retention, sustained release, and penetration across the mucus barrier ( Sung et al, 2007 ). Clinical studies of liposomal curcumin, microparticle curcumin, and micelle curcumin by oral delivery have been found to be safe ( Yallapu et al, 2015 ) and shown to be effective in reducing markers of oxidative stress ( Helli et al, 2021 ). Animal studies have shown that inhalable curcumin effectively mitigates lethal bacterial pneumonia ( Zhang et al, 2019 ).…”
Section: Nanoformulation Of Curcumin For Pulmonary Delivery: An Altermentioning
confidence: 99%
“…Studies have shown that administration of 80-120 mg/day of nano-curcumin can improve patients with type two diabetes, [90][91][92] heart disease, 93 NAFLD, 94 lipid profile, 90,[93][94][95] and hemodialysis. 95,96 Nano-curcumin can exert these protective effects through its antioxidant and anti-inflammatory properties.…”
Section: Effect Of Nano-curcumin On Chronic Diseasesmentioning
confidence: 99%
“…This pathway has an important function in the inflammatory process of the formation, progression, and rupture of atherosclerotic plaque by inhibiting MMPs activity. [98][99][100][101] Other studies indicated that administering 80 mg/day of nano-curcumin could ease diabetic complications, such as neuropathy and nephropathy. Patients who consumed nano-curcumin had decreased HbA1C, fasting blood glucose, estimated average glucose, 90 neuropathy scores, reflex score, foot pain, numbness, weakness, pinprick, temperature, light touch, vibration, 87 hs-CRP, 92 malondialdehyde (MDA), 90,102 and serum lipid parameters include TG, VLDL, total cholesterol, and LDL.…”
Section: Effect Of Nano-curcumin On Chronic Diseasesmentioning
confidence: 99%